Investigation on structure and properties of brass casting - Haque, Md. Mohafizul; Khan, Ahsan Ali (Elsevier, 2008)
In this work, alpha (a) brass was poured in green sand mould and metallic chill mould at about 1050°C. Sand casting method and metallic chill casting method are representing the slow and fast cooling rates of the castings, respectively. The slow cooling rate in the sand mould produces larger grains, while the metallic chill mould produces smaller grains in the castings. As the grain size decreases, the strength of the cast brass increases; micro-porosity in the casting decreases and the tendency for the casting to fracture during solidification decreases. Thus, the faster cooling rate casting offers higher strength, density and hardness compared to the slow cooling rate casting.